2010
DOI: 10.1208/s12248-010-9195-z
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Structure–Activity Relationship for Translocation of Tripeptides via the Human Proton-Coupled Peptide Transporter, hPEPT1 (SLC15A1)

Abstract: Abstract. The human intestinal proton-coupled peptide transporter, hPEPT1 (SLC15A1), has been identified as an absorptive transporter for both drug substances and prodrugs. An understanding of the prerequisites for transport has so far been obtained from models based on competition experiments. These models have limited value for predicting substrate translocation via hPEPT1. The aim of the present study was to investigate the requirements for translocation via hPEPT1. A set of 55 tripeptides was selected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…The recently characterized and validated MDCK/hPEPT1 FLIPR ® membrane potential assay (Molecular Devices, Berkshire, UK) (Faria et al ., 2004; Frolund et al ., 2010; Omkvist et al ., 2010) was used to measure substrate transport via hPEPT1. Gly‐Sar and ibuprofen were applied to the MDCK/hPEPT1 FLIPR ® membrane potential assay in absence or presence of the recently identified high affinity hPEPT1 inhibitor, Met‐Pro‐Pro (Omkvist et al ., 2010). Growth media were aspirated and replaced with 50 µl of FLIPR ® membrane potential assay kit dye stock solution reconstituted in HBSS buffer pH 6.0.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recently characterized and validated MDCK/hPEPT1 FLIPR ® membrane potential assay (Molecular Devices, Berkshire, UK) (Faria et al ., 2004; Frolund et al ., 2010; Omkvist et al ., 2010) was used to measure substrate transport via hPEPT1. Gly‐Sar and ibuprofen were applied to the MDCK/hPEPT1 FLIPR ® membrane potential assay in absence or presence of the recently identified high affinity hPEPT1 inhibitor, Met‐Pro‐Pro (Omkvist et al ., 2010). Growth media were aspirated and replaced with 50 µl of FLIPR ® membrane potential assay kit dye stock solution reconstituted in HBSS buffer pH 6.0.…”
Section: Methodsmentioning
confidence: 99%
“…Translocation via hPEPT1 is electrogenic and changes in membrane potential may thus be used as a surrogate marker for substrate transport. The recently characterized and validated MDCK/hPEPT1 FLIPR ® membrane potential assay (Molecular Devices, Berkshire, UK) Frolund et al, 2010;Omkvist et al, 2010) was used to measure substrate transport via hPEPT1. Gly-Sar and ibuprofen were applied to the MDCK/hPEPT1 FLIPR ® membrane potential assay in absence or presence of the recently identified high affinity hPEPT1 inhibitor, Met-Pro-Pro (Omkvist et al, 2010).…”
Section: Fluorescence-based Studies Of Hpept1 Translocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, chemometric and cheminformatic tools commonly used in drug discovery can be used to elucidate quantitative structure‐property relationships (QSPR), as well as to discredit rules only derived from physical principles …”
Section: Introductionmentioning
confidence: 99%
“…The study found that 40 out of 55 tripeptides were translocated, 8 interacted with the assay used, and one (Met-Pro-Pro) was an inhibitor while one (Asp-Ile-Arg) was not recognized by hPEPT1. 31 A series of benzyl esters of the ketomethylene dipeptidomimetics Phe-ψ[COCH 2 ]Asp, Val-ψ[COCH 2 ]-Asp and Asp-ψ[COCH 2 ]Gly were also shown to display affinity for hPEPT1 and were transported through Caco-2 cell monolayers. 14 It could appear that most ligands are also substrates for the transporter, however, none of the antimicrobial di- and tripeptides tested in a recent study were substrates for hPEPT1 despite having moderate affinity towards the transporter for some of the peptides.…”
mentioning
confidence: 99%